Therapeutic device to ameliorate stuttering - Rastatter, Michael P.; Kalinowski, Joseph Stanley; Stuart, Andrew (East Carolina University, 1999)
A device and method for ameliorating stuttering by providing an altered auditory feedback by employing a compact device configured for positioning in or adjacent the ear canal of an individual. The portable, self-contained device can be used on a chronic basis and includes a receiver for receiving auditory signals, an auditory delay and or frequency shift circuit, and a transmitter for transmitting the altered signal to the individual user.
United States patent 5,961,443
Keywords: Stuttering--Treatment--Patents; Audiology--Instruments--Patents; Stuttering--therapy